Water–energy–carbon nexus at campus scale: Case of North China University of Water Resources and Electric Power. (July 2022) - Li, Ruishi; Zhao, Rongqin; Xie, Zhixiang; Xiao, Liangang; Chuai, Xiaowei; Feng, Mengyu; Zhang, Huifang; Luo, Huili
Abstract: Clarifying the nexus between water, energy, and carbon has great importance regarding regional sustainable development. A university campus is a multifunctional comprehensive community attribute suitable for exploring campus–scale water–energy–carbon nexus and its spatial heterogeneity. In this study, a theoretical framework of the water–energy–carbon nexus at campus scale was established, the spatial patterns of carbon sources/sinks were estimated, and the characteristics of the water–energy–carbon nexus of different functional areas were investigated. Results showed that campus carbon emission and absorption was 32, 119.92 and 557.04 t, respectively. Heat and electricity consumption were the main sources of carbon emissions. Monthly energy–water consumption and carbon emission showed fluctuating trends. Spatial visualization revealed that the highest (lowest) carbon emission was related to the residential (experimental) area. The water–energy–carbon nexus varied among different functional areas, determined primarily by the properties of buildings, energy structure, population density, and human behavior. This research outlines a new policy for low–carbon emission campuses management. Formulating integrated strategies that could help reduce carbon emissions and enhance energy–water saving would contribute to multiobjective realization and promotion of campus sustainability. Highlights: Theoretical framework of water–energy–carbon nexus at campus level was established. Heat and electricity consumption are main sources of NCWU campus carbon emissions. Spatial carbon sources/sinks of different functional areas were visualized. Water–energy–carbon nexus characteristics vary among different functional areas. Policies for promoting both carbon emission and water–energy saving of campus were proposed.